2018
DOI: 10.1021/acsanm.8b00494
|View full text |Cite
|
Sign up to set email alerts
|

Light-Confining Nanoporous Anodic Alumina Microcavities by Apodized Stepwise Pulse Anodization

Abstract: Light-confining nanoporous anodic alumina microcavities by apodized stepwise pulse anodization

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

6
4

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 64 publications
0
20
0
Order By: Relevance
“…Recent developments in pulse anodization technology have aimed at improving light control quality of NAA-PCs. Optimal structural engineering of NAA-µCVs has shown that these NAA-PCs can achieve outstanding light-confining capabilities, with resonance bands achieving unprecedented quality factors as high as 113 49 and 170 50 . A variety of sinusoidal pulse anodization strategies have been explored to improve the quality of light control in NAA-GIFs, including implementation of apodization functions into anodization profiles 51 and application of anodizing voltage as a function of optical path length 52 .…”
Section: Introductionmentioning
confidence: 99%
“…Recent developments in pulse anodization technology have aimed at improving light control quality of NAA-PCs. Optimal structural engineering of NAA-µCVs has shown that these NAA-PCs can achieve outstanding light-confining capabilities, with resonance bands achieving unprecedented quality factors as high as 113 49 and 170 50 . A variety of sinusoidal pulse anodization strategies have been explored to improve the quality of light control in NAA-GIFs, including implementation of apodization functions into anodization profiles 51 and application of anodizing voltage as a function of optical path length 52 .…”
Section: Introductionmentioning
confidence: 99%
“…The optical features of the characteristic PSB in NAA-PCs can be modulated with precision by engineering their nanoporous structure in the form of different PC architectures, including distributed Bragg reflectors (DBRs), 11,47 bandpass filters, 48,49 Fabry-Pérot interferometers, 50,51 gradient-index filters, 10,[52][53][54] hybrid photonic crystals, 55 and optical microcavities. [56][57][58] NAA-PCs have been used in optical chemoand biosensing, 50,51 light filtering, 47 optical encoding 54 and photocatalysis. 10,11 The nanoporous structure of NAA-PCs facilitates mass transfer of ionic and molecular species involved in photocatalytic reactions and an efficient management of photons by controlled light-matter interactions to increase photon-to-electron conversion rates for high-performance photocatalytic applications.…”
Section: Introductionmentioning
confidence: 99%
“…NAA produced by anodization of aluminium is the most researched EENM in the development of PC structures. Forms of NAA-PC structures include Fabry-Pérot interferometers (NAA-FPIs) [141][142][143], distributed Bragg reflectors (NAA-DBRs) [144][145][146], gradient index filters (NAA-GIFs) [147][148][149], optical microcavities (NAA-µCVs) [158][159][160], apodized DBRs and GIFs (Apo-NAA-DBRs and Apo-NAA-GIFs) [161][162][163], bandpass filters (NAA-BPFs) [164] and linear variable bandpass filters (NAA-LVBPFs) [165]. The architecture and geometric features of NAA-PCs can be engineered with precision by pulse-like anodization under mild anodization conditions (i.e., low anodization voltage/current density and moderate acid electrolyte temperatures).…”
Section: Structural Engineering Of Nanoporous Materialsmentioning
confidence: 99%